2004
DOI: 10.1111/j.1432-1033.2004.04099.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein L22 inhibits regulation of cellular activities by the Epstein‐Barr virus small RNA EBER‐1

Abstract: Epstein-Barr virus (EBV) is a potent mitogenic and antiapoptotic agent for B lymphocytes and is associated with several different types of human tumour. The abundantly expressed small viral RNA, EBER-1, binds to the growth inhibitory and pro-apoptotic protein kinase R (PKR) and blocks activation of the latter by double-stranded RNA. Recent evidence has suggested that expression of EBER-1 alone in EBV-negative B cells promotes a tumorigenic phenotype and that this may be related to inhibition of the proapoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…First, replication of vesicular stomatitis virus, a virus sensitive to the antiviral function of PKR (37), is equivalent in B-cell lines immortalized with either a wild-type EBV or a mutant virus lacking the EBER genes and is equivalently repressed in both lines by IFN-␣ treatment (38). Second, the EBERs are normally in a complex with rpL22, an interaction that in vitro can exclude binding by PKR (4), and third, activation of PKR is not prevented upon infection of EBV/EBERpositive cells with mutant adenovirus that does not express the PKR-inhibiting VAI small RNA (43). We conclude, therefore, that EBER inhibition of IFN-␣-induced apoptosis in latently infected cells must occur downstream of PKR activation.…”
Section: Ebv and Eber Inhibition Of Ifn-␣-induced Apoptosismentioning
confidence: 85%
“…First, replication of vesicular stomatitis virus, a virus sensitive to the antiviral function of PKR (37), is equivalent in B-cell lines immortalized with either a wild-type EBV or a mutant virus lacking the EBER genes and is equivalently repressed in both lines by IFN-␣ treatment (38). Second, the EBERs are normally in a complex with rpL22, an interaction that in vitro can exclude binding by PKR (4), and third, activation of PKR is not prevented upon infection of EBV/EBERpositive cells with mutant adenovirus that does not express the PKR-inhibiting VAI small RNA (43). We conclude, therefore, that EBER inhibition of IFN-␣-induced apoptosis in latently infected cells must occur downstream of PKR activation.…”
Section: Ebv and Eber Inhibition Of Ifn-␣-induced Apoptosismentioning
confidence: 85%
“…There is no published evidence to support a role for most genes in the region (Table 1) as TSGs in cancer generally, or neuroblastomas in particular. RPL22 recruits the EpsteinBarr early RNA and is linked to lymphoma associated with Epstein-Barr virus (Elia et al, 2004;Fok et al, 2006). ICMT is an isoprenylcysteine methyltransferase that has been implicated in carcinogenesis and as a target for anticancer therapy (Bergo et al, 2004;WinterVann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of EBER-positive and -negative viruses demonstrated that the small RNA contributes significantly to the efficiency of EBV growth transformation of B cells (385). Ribosomal protein L22 competes with PKR for binding to RNA, thereby halting the PKR inhibition by EBER-1 (89). As a result of this competition, L22 interferes with the ability of the small RNA to inhibit PKR activation by dsRNA, suggesting that L22 may exert a protective effect in vivo against the transforming potential of EBER-1 and EBV.…”
Section: Herpesviruses (I) Hsv-1mentioning
confidence: 99%